GLOBAL RESEARCH PUBLICATION ON DEMOCRACY IN INDONESIA: A BIBLIOMETRIC REVIEW AND SCIENTIFIC VISUALIZATION - Abd Rasyid, Syamsul Bahri; Misran, Misran; Subekti, Dimas (Natapraja, 2025)
Since gaining independence in 1945, Indonesia has experienced several forms of democracy, each prevailing during different political periods and continuing to evolve to the present day. These shifts in democratic practice have spurred scholarly interest across disciplines. This study aims to analyze the development of research on democracy in Indonesia from 1958 to 2021. This research uses bibliometric analysis to map scholarly publications on democracy in Indonesia. 861 scientific journal articles indexed in the Scopus database were analyzed. The data were processed and visualized using VOSviewer and NVivo 12 Plus software to identify patterns, trends, and key contributors in the field. The analysis revealed that 2020 marked the highest number of research publications on democracy in Indonesia. Indonesia contributes the most to this field, while Democratization is the journal with the most relevant publications. Mietzner is identified as the most prolific author in this area of study. Several topics emerged as dominant or emerging areas within the field, including citizenship, presidentialism, minority rights, civil-military relations, patronage, ethnicity, and institutionalization. These areas present significant opportunities for further investigation.